Public Opinions Impacts on Cryptocurrency Valuation: A View from Behavioral Finance Perspective - Gusev, Andrey A. (Journal of Reviews on Global Economics, 2018)
Many fintech start-ups participant companies and cryptocurrencies have experienced phenomenal growth in value during the past several years. Many specialists would like to know the reasons for such success. In this article we investigate the predictive power of public opinions. This is one of the few works that using quantitative analysis connects social media and internet users’ activities with cryptocurrency valuations.